The capture - Lasky, Kathryn (New York : Scholastic, 2003)
When Soren is pushed from his family's nest by his older brother, he is rescued from certain death on the forest floor by agents from a mysterious school for orphaned owls, St. Aggie's.
RL4.
008-012.
730
Accelerated Reader AR
Keywords: Owls -- Juvenile fiction; Fantasy fiction